THE ROLE OF HISTORY TEACHERS IN SHAPING THE CHARACTER OF LOVE FOR THE COUNTRY OF CLASS X STUDENTS OF SURULANGUN STATE SENIOR HIGH SCHOOL - Ayu Wulandari; Supriyanto Supriyanto; Agus Susilo (Universitas Labuhanbatu, 2023)
The purpose of this research is to describe the role of the History Teacher in the formation of the character of loving the motherland. In the research method used is qualitative research with a descriptive approach. The subjects in this study were the teachers and students of SMA Negeri Surulangun. The collection of data used is the first observation, interviews, documentation and the last questionnaire. The results of the study show that (1) the role of the history teacher in forming the character of students' love for the homeland is the teacher as a guide, educator, adviser, motivator, mediator and evaluator. (2) the obstacles encountered by the teacher in the process of forming the character of loving the homeland include learning media, lack of enthusiasm for learning.Keywords: The Rolee of the History Teacher, The Characeter off Love for the MotheerlandÂ Abstrak Tujuan dari penelitian ini adalah untuk mendeskripsikan peran Guru Sejarah dalam pembentukan karakter cinta tanah air. Dalam penelitian ini metode yang digunakan adalah penelitian kualitatif dengan pendekatan deskriptif. Subjek dalam penelitian ini adalah guru dan siswa SMA Negeri Surulangun. Pengumpulan data yang digunakan adalah yang pertama observasi, wawancara, dokumentasi dan yang terakhir angket. Hasil penelitian menunjukkan bahwa (1) peran guru sejarah dalam membentuk karakter cinta tanah air siswa adalah guru sebagai pembimbing, pendidik, penasehat, motivator, mediator dan evaluator. (2) kendala yang dihadapi guru dalam proses pembentukan karakter cinta tanah air antara lain media pembelajaran, kurangnya semangat belajar.Kata kunci: Peran Guru Sejarah, Karakter Cinta Tanah Air